PERANAN SRABI SEBAGAI MAKANAN KHAS UNTUK MEPERTAHANKAN NILAI KEARIFAN LOKAL - Tri Rinawati; Rita Meiriyanti; Diana Puspitasari (Universitas Semarang, 2017)
Local wisdom about traditional food contained in the archipelago, especially the Javanese script is a legacy of high-value ancestors because by inheriting the tradition of food, can strengthen the identity and identity of the Indonesian nation universally.This research uses qualitative method with phenomenology approach. Data collection is done on observation (participant observation), in depth interview (in depth interview) and documentation. Data analysis is data reduction, display data and conclusion drawing / verification. Test the credibility of the data with triangulation and member check. The potential of srabi as a typical food in Ngampin Ambarawa Village is as a source of family income. The traders srabi get additional income by selling the srabi. Sales turnover will increase during holidays and during celebrations of the familiar traditions of Sha'ban moon better known as